SEC targets broker-dealer implications of transaction-based deal fees. Issue 4 (7th November 2016) - Daniel, Jason
Abstract : Purpose: To explain a US Securities and Exchange Commission (SEC) enforcement action against a registered investment adviser to private equity funds for allegedly providing brokerage services in connection with the acquisition and disposition of the securities of portfolio companies while not being registered as a broker dealer, making undisclosed use of fund assets, and failing to adopt policies and procedures designed to prevent the alleged violations. Design/methodology/approach: Describes the services provided by the investment adviser, the compensation paid, and the SEC's other bases for enforcement, and draws conclusions for private equity fund advisers. Findings: The SEC has begun pursuing transaction-based compensation paid to private equity fund advisers relating to portfolio company transactions as illegal brokerage commissions. The Commission also continues to target the adviser's undisclosed use of client fund capital, especially in private equity funds. Originality/value: Practical explanation by experienced investment management lawyer.